Real Time Observation of Lithium Insertion into Pre-Cycled Conversion-Type Materials - Sooyeon Hwang; Dong Su (Nanomaterials, 2021)
Conversion-type electrode materials for lithium-ion batteries experience significant structural changes during the first discharge–charge cycle, where a single particle is taken apart into a number of nanoparticles. This structural evolution may affect the following lithium insertion reactions; however, how lithiation occurs in pre-cycled electrode materials is elusive. In this work, in situ transmission electron microscopy was employed to see the lithium-induced structural and chemical evolutions in pre-cycled nickel oxide as a model system. The introduction of lithium ions induced the evolution of metallic nickel, with volume expansion as a result of a conversion reaction. After pre-cycling, the phase evolutions occurred in two separate areas almost at the same time. This is different from the first lithiation, where the phase change takes place successively, with a boundary dividing the reacted and unreacted areas. Structural changes were restricted at the areas having large amount of fluorine, implying the residuals from the decomposition of electrolytes may have hindered the electrochemical reactions. This work provides insights into phase and chemical evolutions in pre-cycled conversion-type materials, which govern electrochemical properties during operation.